Experimental study on improving cement quality with oxygen- enriched combustion technology. Issue 1 (November 2015) - Liu, Y Q; Zhang, A M; Qing, S; Li, F S; Yang, S P; Yang, Z F
Abstract: With the intensification of the global energy crisis, the production cost of enterprises is continuously increasing because of the rising fuel prices and high requirements for environmental protection. As result, energy savings and environmental protection are vital considerations for a variety of enterprises. As a practical energy-saving technology, oxygen- enriched combustion has played a major role in energy saving and emissions reduction as its application in industrial furnaces has been popularized in recent years. This experiment was conducted in a cement rotary kiln with a capacity of 4000 t/d in a factory in China. Based on measured data in the oxygen-enriched combustion experiment, we determined the patterns of variation in the main parameters of the cement rotary kiln under oxygen-enriched production conditions. The results provide important theoretical and practical base for the cement building materials industry in energy saving and emissions reduction.